Analisis Perencanaan Strategi Pada Raudhatul Athfal (RA) Al-Falah - Ani Hidayati (ARBITRASE: Journal of Economics and Accounting, 2022)
Strategic planning can be done by conducting an external analysis using PESTEL (Political, Economic, Social, Technological, Environmental, Legal) and Porter's Five Forces analysis. SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) is conducted to determine the internal capabilities and external capabilities of the organization in strategic planning. This research aims to find out; what are the external factors of RA Al-Falah with PESTEL analysis? What are the external factors of RA Al-Falah with Porter's Five Forces analysis? What are the internal and external factors of RA Al-Falah with SWOT analysis? What factors influence RA Al-Falah with PESTEL analysis? What factors influence RA Al-Falah with Porter's Five Forces analysis? and What factors influence RA Al-Falah with SWOT analysis? The object of this study is the management of Raudhatul Athfal (RA) Al-Falah. The results of the study can be concluded that: (1) economic, social, technological, environmental and legal influences RA Al-Falah, (2) Raudhatul Athfal (RA) Al-Falah has a high threat of substitute products or services and low supplier power, ( 3) strategies that can be carried out by RA Al-Falah include (a) providing opportunities for teachers to take part in various training/workshops related to the implementation of the Independent Curriculum, (b) using social media as a means of introducing or promoting schools, such as Instagram, (c) collaborating with side prayer rooms schools in the use of land for parking, (d) providing a regular budget to increase the use of IT (internet), (e) supporting the settlement of legal cases faced by the Foundation by providing the requested information according to known facts. (f) increasing motivation for parents of students to carry out school promotions (word of mouth).